2012
DOI: 10.1371/journal.pone.0037932
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Inflammatory Bowel Disease Exhibit Dysregulated Responses to Microbial DNA

Abstract: BackgroundA critical role for the gut epithelium lies in its ability to discriminate between pathogens and commensals and respond appropriately. Dysfunctional interactions between microbes and epithelia are believed to have a role in inflammatory bowel disease (IBD). In this study, we analyzed microbiota and gene expression in IBD patients and examined responses of mucosal biopsies to bacterial DNA.MethodsBiopsies were taken from non-inflamed areas of the colon in healthy controls (HC) and Crohn's disease (CD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…A recent meta-analysis of IBD genetic studies identified 163 IBD risk loci (4), and many of these risk alleles exhibit infection-related balancing natural selection (4). Consistent with this finding, an overall dysfunction in the human gut microbial community has been described in both longstanding adult-onset IBD (5) and treatment-naive pediatric-onset IBD (6), and patients exhibit altered responses to bacterial DNA (7). Animal models have conclusively shown causality in the requirement for bacterial colonization in the development of intestinal inflammation in genetically susceptible hosts (3).…”
Section: Introductionmentioning
confidence: 80%
“…A recent meta-analysis of IBD genetic studies identified 163 IBD risk loci (4), and many of these risk alleles exhibit infection-related balancing natural selection (4). Consistent with this finding, an overall dysfunction in the human gut microbial community has been described in both longstanding adult-onset IBD (5) and treatment-naive pediatric-onset IBD (6), and patients exhibit altered responses to bacterial DNA (7). Animal models have conclusively shown causality in the requirement for bacterial colonization in the development of intestinal inflammation in genetically susceptible hosts (3).…”
Section: Introductionmentioning
confidence: 80%
“…Moreover, recent studies suggest that the normal immune interactions between TLR9 and NOD2 are lost in CD patients [28], [29]. NOD2 is a cytosolic innate immune receptor that mediates pro-inflammatory and antibacterial responses through recognition of bacterial cell wall components.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were particularly focused on how dysregulation of TLR9 signaling could lead to the development of inflammatory bowel disease or colitis (Rachmilewitz et al 2004; Katakura et al 2005; Lee et al 2006; Luther et al 2011; Hotte et al 2012; Jounai et al 2012; O’Hara et al 2012; Owyang et al 2012). …”
Section: Tlr9 Functions In the Innate Immune Responsementioning
confidence: 99%